2018
DOI: 10.1097/mpg.0000000000002148
|View full text |Cite
|
Sign up to set email alerts
|

There Is No Excuse for Mortality Due to Lack of Competency and Training of Paediatric Endoscopists in Gastrointestinal Bleeding Therapy in 2018

Abstract: Acute upper gastrointestinal bleeding in children is possibly the last medical emergency which continues to lead to the death of a child due to the lack of competency/clinical judgement of the doctor, as opposed to the disease itself, leading to mortality despite optimum medical intervention. This is unacceptable in any circumstances in 2018. It occurs due to a number of conspiring factors including lack of appreciation of the clinical presentation requiring urgent endoscopic intervention; misapprehension of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A recent survey of pedia-tric endoscopy in the UK pointed out that only 50 % of tertiary centers for pediatric endoscopy could provide a valuable service to face upper GI bleedings [2]. This important issue is exhaustively addressed in a recent review [3].…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey of pedia-tric endoscopy in the UK pointed out that only 50 % of tertiary centers for pediatric endoscopy could provide a valuable service to face upper GI bleedings [2]. This important issue is exhaustively addressed in a recent review [3].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that the number of procedures in the paediatric population is not sufficient to reach the minimum number of procedures recommended to reach competency . In 2018, Thomson et al reported a lack of endoscopy training and knowledge to adequately treat gastrointestinal bleeds in the paediatric population in Europe leads to increased mortality of ‘save‐able’ lives . Questions regarding this phenomenon remain in paediatric gastroenterology.…”
Section: Discussionmentioning
confidence: 99%